Effect of Deep Brain Stimulation on Cerebellar Tremor Compared to Non-Cerebellar Tremor Using a Wearable Device in a Patient With Multiple Sclerosis: Case Report - Xie, Tao; Padmanaban, Mahesh; Javed, Adil; Satzer, David; Towle, Theresa E.; Warnke, Peter; Towle, Vernon L. (Frontiers in Human Neuroscience, 2022)
Tremor of the upper extremity is a significant cause of disability in some patients with multiple sclerosis (MS). The MS tremor is complex, in that it contains an ataxic intentional tremor component due to the involvement of the cerebellum and cerebellar outflow pathways by MS plaques, which makes the MS tremor in general less responsive to medications or deep brain stimulation (DBS) than those associated with essential tremor or Parkinson’s disease. The cerebellar component has been thought to be the main reason for making DBS less effective, although it is not clear whether it is due to the lack of suppression of the ataxic tremor by DBS or else. The goal of this study was to clarify the effect of DBS on cerebellar tremor compared to non-cerebellar tremor in an MS patient. By wearing an accelerometer on the index finger of each hand to quantitatively characterize action tremor by frequency and amplitude with cerebellar ataxia component on one hand and that without cerebellar component on the other hand at the beginning and end of the hand movement approaching a target at DBS Off and On status, we found that cerebellar tremor surprisingly had a good response to DBS as did for tremor without a cerebellar component, but the function control on cerebellar tremor was not as good due to its distal oscillation which made the amplitude of tremor increasingly greater as it approached the target. This explains why cerebellar tremor or MS tremor with cerebellar component has a poor functional transformation even with good percentage of tremor control. This case study provides a better understanding of the effect of DBS on cerebellar tremor and MS tremor, which may improve patient selection and outcome prediction for DBS treatment.